Pengaruh Metode Emo-Demo terhadap Pengetahuan, Motivasi, dan Self-Efficacy Ibu Mengenai Praktik Pemberian ASI Eksklusif di Wilayah Kerja Puskesmas Sumowono: The Effect of the Emo-Demo Method on Mothers' Knowledge, Motivation, and Self-Efficacy Regarding Exclusive Breastfeeding Practices in the Sumowono Community Health Center Working Area - Idroes, Syarifah Zahwana Tasya Al; Pangestuti, Dina Rahayuning; Rahfiludin, Mohammad Zen (Amerta Nutrition, 2024)
Background: Breast milk is the main source of nutrition for newborns up to six months of age. Data from Statistics Indonesia (BPS) shows a decline in the number of infants receiving exclusive breastfeeding in Central Java. This study aimed to see the effect of the Emo-Demo method on mothers' knowledge, motivation, and self-efficacy regarding exclusive breastfeeding practices in the Sumowono Community Health Center Working Area. Objectives: This study aimed to determine the effect of the application of the Emo-Demo method on mothers' knowledge, motivation, and self-efficacy regarding exclusive breastfeeding practices in the intervention and control groups. Methods: The study employed a quasi-experimental pretest-posttest control group design, involving 71 respondents: 43 mothers in an intervention group and 28 mothers in a control group. The research instruments included an interview guide, research questionnaires, Emo-Demo method modules, a microtoise, and a digital scale. Data was analyzed using univariate and bivariate methods (Mann-Whitney and Wilcoxon tests). Results: The Emo-Demo method improved mothers' knowledge and motivation, implying that there were significant effects on both knowledge (<0.001) and motivation (<0.001) between groups. In contrast, there were no significant effects on self-efficacy (0.070) and exclusive breastfeeding practices (0.439) between groups. Conclusions: The Emo-Demo method was effective in measuring the knowledge and motivation of mothers in the Sumowono Community Health Center Working Area.